Students' e-skills, organizational change and diversity of learning processs: Evidence from French universities in 2010 - Adel Ben Youssef; Mounir Dahmani; Nessrine Omrani (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Driven by ICT, universities are changing in depth the nature and forms of learning processes, which are intended to prepare students to a better entry into the labour market. In this paper, we focus on the evolution of students' use of ICT in such an institution characterized by organizational changes and we analyse the determinants of students' e-skills using a 2010 dataset of French university students. We show that students' involvement in the use of ICT increases their e-skills. ICT learning by doing and ICT learning by using also increase some categories of students' e-skills. In addition, collaborative and cooperative learning are positively associated with students' advanced e-skills.
urn:nbn:de:bsz:180-madoc-323052
Keywords: 330; Students; ICT; E-skills; Multinomial logit model; Labour market; New Organizational Practices; Studierende; Computerunterstützung; Qualifikation; Lernprozess; Organisatorischer Wandel; Frankreich